2017
DOI: 10.3122/jabfm.2017.04.170084
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians' Perceptions of Electronic Cigarettes in Tobacco Use Counseling

Abstract: Background: Recent support has been shown for physicians to recommend e-cigarettes to patients who are trying to quit smoking. Supporters of this recommendation argue that e-cigarettes are not combustible products and are less harmful and more effective cessation products than regular cigarettes, with less inherent risk. Those who oppose this idea argue that little reliable evidence suggests that e-cigarettes are better cigarette cessation devices than currently available nicotine replacement therapies, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 23 publications
4
53
2
2
Order By: Relevance
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
“…The majority of research on HP–smoker discussions about NVPs comes from cross‐sectional and qualitative surveys of physicians. These studies have indicated that dialogues about NVPs have become increasingly frequent in clinical settings , are generally initiated by the patient , and typically do not end in a recommendation to use NVPs, apparently because most providers remain neutral or advise against use . To the best of our knowledge, only two studies have examined patient–physician NVP discussions from the patient's perspective .…”
Section: Introductionmentioning
confidence: 99%
“…Standard descriptive statistics, Fisher exact test, and Kruskal-Wallis test were used to analyze the quantitative data. The study team analyzed the content of the openended responses (qualitative data) individually and in two team meetings using an immersion-crystallization approach [20][21][22] -a dual process involving detailed review of textual data and momentarily suspending the immersion process to reflect on emerging findings until consistent themes are identified. 20,21…”
Section: Methodsmentioning
confidence: 99%
“…Estos datos del presente estudio se pueden deber al auge del uso de cigarrillos electrónicos, como puede verse en varios estudios en universitarios (Copeland, Peltier y Waldo, 2017;Rakotozandry et al, 2016) y jóvenes en general (Carroll y Wu, 2014;Peiper et al, 2016) donde afirman que ha aumentado el uso de este dispositivo en jóvenes y abalan el uso del cigarrillo electrónico como medida para dejar de fumar tabaco, sobretodo en jóvenes. En contraposición, otras investigaciones (Brose, Hitchman, Brown, West y McNeill, 2015;Córdoba, 2014;Ofei-Dodoo, Kellerman, Nilsen, Nutting y Lewis, 2017;Shi et al, 2016;Sutfin, McCoy, Morrell, Hoeppner y Wolfson, 2013) no consideran el uso de cigarrillos electrónicos como medida para dejar de fumar, pero sí para reducir el consumo.…”
Section: Discussionunclassified